2020
DOI: 10.1021/acsami.0c03563
|View full text |Cite
|
Sign up to set email alerts
|

Interface Study on the Effect of Carbon and Boron Carbide Diffusion Barriers in Sc/Si Multilayer System

Abstract: Sc/Si multilayers are one of the promising material combinations commonly used in the spectral range of 35−50 nm. However, diffusion and silicidation at the interfaces of Sc/Si multilayers limit widespread applications of this material combination. To improve the properties of Sc/Si multilayers, the scheme of barrier layers is utilized. In this work, a series of Sc/Si multilayers with boron carbide and carbon barrier layers were designed and fabricated to compare the properties including interface quality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Therefore, suppression or even full illumination of the intermixing is crucial for the improvement of the reflectivity of PMMs. In addition, the knowledge about intermixing mechanisms in Sc/Si and Co/C PMMs developed in early studies [37][38][39] allowed suppression of the intermixing by introducing diffusion barriers and improved the temperature stability of PMMs [41][42][43]. In addition to the intermixing, the interface roughness is another fac reflectivity.…”
Section: Structural and Optical Propertiesmentioning
confidence: 99%
“…Therefore, suppression or even full illumination of the intermixing is crucial for the improvement of the reflectivity of PMMs. In addition, the knowledge about intermixing mechanisms in Sc/Si and Co/C PMMs developed in early studies [37][38][39] allowed suppression of the intermixing by introducing diffusion barriers and improved the temperature stability of PMMs [41][42][43]. In addition to the intermixing, the interface roughness is another fac reflectivity.…”
Section: Structural and Optical Propertiesmentioning
confidence: 99%
“…Therefore, suppression or even full illumination of the intermixing is crucial for the improvement of the reflectivity of PMMs. Besides, the knowledge about intermixing mechanisms in Sc/Si and Co/C PMMs developed in early studies [37] [38] [39] allowed suppression of the intermixing by introducing diffusion barriers and improve the temperature stability of PMMs [41] [42,43]. [44] with permission from Elsevier.…”
Section: Structural and Optical Propertiesmentioning
confidence: 99%
“…To date, there have not been many reports comparing how the interfacial microstructure evolves or the layer contrast is restored when C or B 4 C is introduced to a particular material combination. Recently, 26 Zhu et al reported a comparison between 0.9 nm thicknesses C and B 4 C BL on a Sc/Si ML of bilayer with a thickness of 23.2 nm, and they found distinct differences between the interfaces in as-deposited as well as as-annealed samples. However, these are high-bilayer-thickness MLs with applications in 35–50 nm X-rays.…”
Section: Introductionmentioning
confidence: 99%